The Transnational Artistic Memorialisation of Operation Condor: Documenting a "Distribution of the Possible". Issue 2 (2nd April 2020) - Preda, Caterina
Abstract : This article analyses three artistic projects that contribute to a transnational artistic memorialisation of Operation Condor: João Pina's project Condor (2005–2014), the documentary film by Pedro Chaskel, De vida y de muerte, testimonios de Operación Condor (2000–2015), and Voluspa Jarpa's En nuestra pequeña región de por acá (2016/2017). Situated at the crossroads of the study of the role of art in Transitional Justice processes and cultural memory studies, this article conceptualises the role of art in forging a transnational memory through the lens of the "art and politics of memory". Using Jacques Rancière's observation of the role of art in building a new "distribution of the sensible", this investigation argues that artistic practices of remembrance employ three strategies. In the first place, they render visible those who are still absent; secondly, they document and provide supplementary sources about human rights abuses during dictatorships, and thus give back human dignity to the victims. Finally, they also criticise the status quo of official memory. In the absence of a transnational memory of the secret cooperation that occurred within Operation Condor, artistic practices of remembrance help build this memory and create a "distribution of the possible".